Family, Peers and Juvenile Delinquency: Analysis of Different Pathways to Recidivism - Cunha, Cláudia; Soares, Mónica; Veríssimo, Lurdes; Matos, Raquel (Revista de Psicología, 2015)
Different family factors such as structure, family dynamics (cf. Contreras, Molina & Cano, 2011) and peer-related variables (cf. Cottle, Lee & Heilbrun, 2001) have been linked to recidivism among young offenders. Bringing new contributions to this discussion, our goal was to evaluate how different family and peer factors of risk differ according to various recidivism pathways (e.g., non-reoffenders; moderate reoffenders; persistent reoffenders). Taking a sample of 105 young offenders, complying with youth justice measures, the present study has been developed in Portugal and focuses on recidivism as an indicator of persistent reoffending. Results showed that more than half of young offenders in the sample (54.3%) are reoffenders, as they have already complied with former youth justice measures. Among the most relevant variables associated with recidivism are a previous connection with the protection system, and the criminal behavior of the young offenders’ peers. Together, these factors may relate to delinquent behavior, highlighting the need to develop integrated interventions, in order to prevent recidivism.